Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/jbmr.1994
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis of Heterotopically Transplanted Mesenchymal Stromal Cells in Rat Models of Chronic Kidney Disease

Abstract: The current study is based on the hypothesis of mesenchymal stromal cells (MSCs) contributing to soft-tissue calcification and ectopic osteogenesis in chronic kidney disease (CKD). Rat MSCs were transplanted intraperitoneally in an established three-dimensional collagen-based model in healthy control animals and two rat models of CKD and vascular calcification: (1) 5/6 nephrectomy þ high phosphorus diet; and (2) adenine nephropathy. As internal controls, collagen gels without MSCs were transplanted in the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
1
22
2
Order By: Relevance
“…Sclerostin is constitutively expressed in the aorta [16][17][18] and up-regulated in foci of vascular and valvular calcification. [19][20][21][22] The function of sclerostin in the vasculature is unknown. Although sclerostin may function as a negative regulator of vascular calcification and sclerostin inhibition could promote vascular calcification, studies have shown conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerostin is constitutively expressed in the aorta [16][17][18] and up-regulated in foci of vascular and valvular calcification. [19][20][21][22] The function of sclerostin in the vasculature is unknown. Although sclerostin may function as a negative regulator of vascular calcification and sclerostin inhibition could promote vascular calcification, studies have shown conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…For the sake of patient safety, any clinical application of MSCs should take into account potential risks, such as ectopic tissue formation [14, 15] and tumor generation caused by malignant transformation of the cells during ex-vivo expansion [16]. After initial reports on the occurrence of neoplastic transformation in ex-vivo expanded huMSCs after long-term culture [16, 17, 18] this event has been subsequently described as uncommon, with an estimated frequency of <10 −9 [19, 20, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Although sclerostin is an established regulator of bone mineralization (17), its potential role in vascular biology and arterial health is less clear. Sclerostin has been detected in the human aorta(18) and is up-regulated in calcifying vascular smooth muscle cells(19, 20) and calcified valvular plaques(21). The relationship of human serum sclerostin and vascular calcification, to our knowledge, has been investigated in four previous studies with two showing a direct correlation with calcification(22, 23) and two reporting an inverse correlation(24, 25).…”
Section: Introductionmentioning
confidence: 99%